ChemInform Abstract: New and Efficient Synthesis of 2, 3, 4‐Trisubstituted 2H‐Pyrrolo[3, 4‐c]quinolines via a MCR/Staudinger/Aza‐Wittig Sequence. Issue 16 (March 2016) - Qu, Feng; Hu, Ruo‐Fei; Gao, Le; Wu, Jing; Cheng, Xiao‐Hong; Wang, Song; He, Ping
Abstract: The multicomponent two‐step reaction of easily accessible 1, 3‐dicarbonyl compounds, 2‐azidobenzaldehyde, nitromethane and aryl or alkylamines provides the title products in high yields.